Komunikasi Ritual Balian Bawo dalam Pengobatan Tradisonal Masyarakat Dayak Dusmala Kalimantan Tengah - Aquarini; Ella Febriani (PT. PENERBIT TIGA MUTIARA, 2023)
The Balian Bawo ritual is a healing ritual carried out by men and is believed by the Dayak community of Dusun Maanyan and Lawangan (Dusmala). In ritual processions, it is closely related to asking for help from ancestors to get healing instructions. This research aims to uncover the ritual communication contained in Balian Bawo, which is communication between ancestors and the Balian Bawo. Researchers used hermeneutical phenomenology methodology by taking 6 people as sources. The data collection techniques used were observation, interviews, and documentation. The results of the research show that Balian Bawo ritual communication is seen in three ways, namely 1. Communication is with communicators, namely Balian and ancestors as communicants to convey messages about healing instructions through the intermediary of sowing rice which then includes dance and the sounds of bracelets as a connecting frequency amplifier; 2. Communion in the Balian Bawo Ritual in traditional medicine occurs not because of periodic activities every year, but is present when people need treatment; and 3. Common means that the local community can help the family prepare for the Balian Bawo Ritual activities and the Balian Bawo ritual procession can be followed by the local community as long as they comply with the existing regulations during the activity procession which is a form of community awareness of the existence of the Balian Bawo healing ritual.